Promoting Electricity-Saving Practices in Urban Office Settings: The Role of Employees in Vietnam’s Banking Sector - Nhung, Vu Cam (International Journal of Energy Economics and Policy, 2025)
This study looks into the key motivators that influence the attitude of bank employees toward electricity-saving, viewed in the light of energy productivity at the workplace and its connection to more general sustainability aims. This study posits a contribution toward the understanding of pro- environmental behavior in the workplace by examining factors, including attitudes, awareness toward electricity- saving, and intention, that influence low-carbon behavior for banking employees. This study makes use of a quantitative research design on details obtained from 405 employees selected by convenience sampling from various levels of hierarchy in the firm. This will provide a varied view of behavioral patterns linked to the use of energy. The findings of this study will bring out the motivation of employees to support the corporate electricity-saving conservation initiative in the prevailing trend of rising importance of environmental concern and strategic significance of employee engagement towards the sustainability drive of the organization. More specifically, subjective standards, perceived behavioral control, sense of responsibility, and cognition of electricity price are factors that influence electricity-saving behaviors among the banking employees in HCMC. These findings show a strong connection between these factors and the actual uptake of the practice by the employees. These insights should, therefore, inform the action of banks in Ho Chi Minh City in taking electricity-saving opportunities while reducing the negative environmental impacts that result from their operations. Moreover, saving on electricity presents organizations with enormous economic benefits due to resultant cost savings, which enhances their competitiveness. In this regard, implementing the findings of this study may help the employees in banking services raise awareness regarding electricity-saving and provide the valuable knowledge for practices as well as scholars.